Pyk2-dependent phosphorylation of LSR enhances localization of LSR and tricellulin at tricellular tight junctions. - Daiki Nakatsu; Fumi Kano; Naeko Shinozaki-Narikawa; Masayuki Murata (PLoS ONE, 2019)
Tight junctions (TJs) are cellular junctions within the mammalian epithelial cell sheet that function as a physical barrier to molecular transport within the intercellular space. Dysregulation of TJs leads to various diseases. Tricellular TJs (tTJs), specialized structural variants of TJs, are formed by multiple transmembrane proteins (e.g., lipolysis-stimulated lipoprotein receptor [LSR] and tricellulin) within tricellular contacts in the mammalian epithelial cell sheet. However, the mechanism for recruiting LSR and tricellulin to tTJs is largely unknown. Previous studies have identified that tyrphostin 9, the dual inhibitor of Pyk2 (a nonreceptor tyrosine kinase) and receptor tyrosine kinase platelet-derived growth factor receptor (PDGFR), suppresses LSR and tricellulin recruitment to tTJs in EpH4 (a mouse mammary epithelial cell line) cells. In this study, we investigated the effect of Pyk2 inhibition on LSR and tricellulin localization to tTJs. Pyk2 inactivation by its specific inhibitor or repression by RNAi inhibited the localization of LSR and downstream tricellulin to tTJs without changing their expression level in EpH4 cells. Pyk2-dependent changes in subcellular LSR and tricellulin localization were independent of c-Jun N-terminal kinase (JNK) activation and expression. Additionally, Pyk2-dependent LSR phosphorylation at Tyr-237 was required for LSR and tricellulin localization to tTJs and decreased epithelial barrier function. Our findings indicated a novel mechanism by which Pyk2 regulates tTJ assembly and epithelial barrier function in the mammalian epithelial cell sheet.